Research of heat and mass transfer processes in conditions of microwave heating of wet wood - Kostoreva Anastasya A.; Kostoreva Zhanna A.; Rogovaya Lidiya V.; Loginov Vladimir S. (MATEC Web of Conferences, 2017)
The results of experimental and theoretical studies of the processes of heat and mass transfer occurring during drying of wood under microwave heating are presented. The times of moisture removal are set. It is established that the dynamics of dehydration depends on the type of wood. Based on the results of experimental studies, a mathematical model of the heat transfer processes taking place under conditions of intensive phase transformations (evaporation of water) is formulated together during the dehydration of the wood. A comparative analysis of the theoretical and experimental values of the drying times showed their satisfactory consistency.